Fundamentals of dimensional metrology - Dotson, Connie (Thomson Delmar, 2006)
Aims to offer a direct path to understanding and applying the principles, techniques, and devices used within the dimensional metrology field. This edition uses both the Metric and Imperial systems, yet emphasizes Metric measurement devices and concepts in all examples.